Defining European Wholesale Electricity Markets: An “And/Or” Approach - Elbert Dijkgraaf; Maarten C.W. Janssen (Tinbergen Institute, 2009)
An important question in the dynamic European wholesale markets for electricity is whether to define the geographical market at the level of an individual member state or more broadly. We show that if we currently take the traditional approach by considering for each member state whether there is one single other country that provides a substitute for domestic production, the market in each separate member state has still to be considered a separate market. However, if we allow for the possibility that at different moments in time there is another country that provides a substitute for domestic production, then the conclusion should be that certain member states do not constitute a separate geographical market. This is in particular true for Belgium, but also for The Netherlands, France, and to some extent also for Germany and Austria. We call this alternative approach the and/or approach.
Keywords: L94; L40; 330; Electricity; convergence; market definition; market coupling; Energiemarkt; Marktgröße; EU-Staaten